Módulo de elasticidad y de rotura a la flexión estática de Pinus taeda de dos procedencias - Winck, Rosa Ángela; Palacio, Mariano; Bragañolo, Adelaida; Belaber, Ector; Gauchat, Maria Elena; Aquino, Diego Rolando; Suirezs, María Teresa (Facultad de Ciencias Forestales, Universidad Nacional de Misiones., 2022)
The objetive of this study was to evaluate the variation of the stiffness and strength properties of wood Pinus taeda from marion and Livingston provenances. Twenty-nine trees wew harvested from a Clonal Seed Orchard located at San Antonio, Misiones, Argentina. From basal logs of 60 cm length, standardized samples were taken between rings 14 and 15 to submit them to static bending tests. The values of modulus of elasticity and modulus of rupture were greater for Livingston provenances. The values of the modulus of elasticiy were 55657 kg/cm2 and 70359 kg/cm2; and of 505 Kg/cm2 and 589 kg/cm2 of modulus of rupture, for Pinus taeda Marion and Livingston, respectively.